EMPOWERING THE ROLE OF MOTHERS THROUGH SELF-SUFFICLENCY TRAINING IN PROCESSED ANCHOVY SAUSAGES (Stolephorus spp.) IN FAMILY COMMUNITIES WITH CHILDREN WITH SPECIAL NEEDS â€œKURNIA ILAHIâ€ IN METESEH SEMARANG - Endah Aryati Ekoningtyas; Ani Subekti; Muflihah Isnawati; Benni Benyamin (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2023)
Physical limitations and intelligence of children with special needs (ABK) cause a lack of maintenance of oral health. Maintenance of dental and oral health that is less than optimal causes children with special needs to experience problems with their teeth and mouth (dental caries). The high prevalence of dental caries causes the masticatory function is not optimal. Dental caries can be prevented by sufficient calcium and fluoride in the teeth, such as the consumption of anchovies. So there is a need for training in the manufacture of processed anchovy sausages for mothers of children with special needs "Karunia Ilahi". This Community Service aims to help parents in processing seafood dishes in order to improve the dental and oral health of children with special needs. The method of implementing the activity begins with the 5- table PosKesGi activity followed by training on making anchovy sausages for 30 women from the â€œKarunia Ilahiâ€ community. After that, the cadres will be monitored for their activities in PosKesGi activities for 1 month. The results obtained were an increase in ABK discipline in brushing teeth. After consuming anchovy sausage, 10% of participants (3 people) experienced itching on the surface of the oral mucosa. Consumption of anchovy as much as 50 grams per day is recommended to optimize bone growth and prevent dental caries